PENGARUH PROGRAM DASAR PEMBANGUNAN DESA TERHADAP PEMBERDAYAAN MASYARAKAT DI DESA TOGUNGGUH DAN DESA TELAGABIRU KECAMATAN TANJUNGBUMI KABUPATEN BANGKALAN - Dewi Sri Nurainingsih (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2019)
This research aims at analyzing the village development program and community empowerment at Togungguh Villagae and Telagabiru Village. It also intends to examine the influence of Village Development Program on those two villages. Village Development Program as the independent variable comprise the aspects of education, health and purchasing power. Meanwhile, community empowerment as the dependent variable covers income raising, community participation, improved skill and knowledge, and improved health. The result shows that the Village Development Program at Tanjungbumi Subdistrict does not optimally perform mainly due to several reasons: the community's insufficient understanding of the importance of balanced nutrients, uneven distribution of cheap basic necessities, and poor infrastructures for elementary and secondary education. These conditions contribute to inconsiderable level of community empowerment. In addition, village administrative officials do not adequately socialize the program to the whole community. Thus, the community do not have the opportunity to utilize the facilities that the government has provided for the development of their income-raising activities. Further more, the community are perceived to be less innovative in developing local potentials.